Pengaruh Tingkat Inflasi dan Harga Emas terhadap Pembiayaan Rahn di PT Pegadaian Syariah Blangpidie - Rahmatan, Fina (Medan Resource Center, 2023)
This article aims to discuss the effect of the inflation rate and the price of gold on rahn financing at Pt Pegadaian Syariah Blangpidie. After the Covid-19 pandemic, the world faced a period of economic inflation and rising gold prices. The economic downturn has forced a number of lending institutions to provide opportunities for business actors to obtain capital loans. PT Pegadaian Syariah which offers loans through Rahn financing. The purpose of this study was to find out the effect of the inflation rate and the price of gold on Rahn's financing at PT Pegadaian Syariah Blangpidie. The sample consists of 30 people. The data collection technique was a questionnaire and the data was analyzed using statistical formulas through the SPSS application. The results of this study indicate that partially the inflation rate has no effect on Ranh's financing at the Sariah Blangpidie Pawnshop and the gold price has a significant effect on Rahn's financing. Meanwhile, the inflation rate and gold price simultaneously have a significant effect on Rahn's payment at PT Pegadaian Syariah Blangpidie